Hipertansiyon Hastalarının İlaç ve Diyet Tedavisine Uyum Düzeyleri - OĞUZ, SIDIKA (My University, 2021)
Amaç: Bu tanımlayıcı araştırma, hipertansiyon hastalarının ilaç ve diyet tedavisine uyum düzeylerini ve uyumu etkileyebilecek bireysel faktörleri incelemek amacıyla yapıldı.Yöntemler: Araştırma, İstanbul’ da bir üniversite hastanesinin Kardiyoloji Polikliniğinde 1 Kasım-31 Aralık 2011 tarihleriarasında, çalışmaya katılmaya istekli ve gönüllü, en az 6 ay önce hipertansiyon tanısı konmuş 250 hasta ile yapıldı. Veriler Hasta Tanıtım Formu, İlaca Uyum Hakkındaki İnançlar Ölçeği (İUHİÖ) ve Diyete Uyum Hakkındaki İnançlar Ölçeğiyle(DUHİÖ) toplandı.Bulgular: Hastaların yaş ortalaması 62.9±1.15 olarak bulundu. Hastaların %65.2’ si kadın, %82’ si evli, %33.2’ si ilköğretimmezunu, %67’ sinin günlük hayatında stresin var olduğu, %44.4’ ünün düzenli egzersiz yaptığı, %55.2’ sinin ailesindehipertansiyon hastalığı olduğu belirlendi.Araştırmamıza katılan hastaların ilaç ve diyet yarar alt boyutlarının puan ortalamaları (İUHİÖ’nin yarar alt boyutu21.44±5.39, DUHİÖ’ nün yarar alt boyutu 23.44±5.50), engel alt boyutları puan ortalamalarından (İUHİÖ’ nin engelalt boyutu 17.52±4.66, DUHİÖ’ nin engel alt boyutu 12.9±3.59) daha yüksek bulunmuştur. Genel olarak çalışmamızakatılan hastaların ilaç tedavisine uyumlarının iyi, diyet tedavisine uyumlarının ise orta düzeyde olduğu bulunmuştur.Araştırmada, ailesinde hipertansiyon olan hastaların ilaç ve diyet tedavisine uyumlu, düzenli egzersiz yapan hastalarındiyet tedavisine uyumlu, ilaç tedavisine uyumsuz, günlük hayatında stresi olan hastaların ise ilaç ve diyet tedavisineuyumsuz olduğu belirlenmiştir (p<0.05).Sonuç: Araştırmaya katılan hastaların ilaç ve diyet tedavisine uyumları iyi düzeydedir. Günlük hayatında stresi olanhastaların ilaç ve diyet tedavisine uyum düzeyleri azalmaktadır. Ailesinde hipertansiyon olan hastalar ilaç ve diyet tedavisine daha uyumludur. Düzenli egzersiz yapan hastalar ilaç tedavisine uyumsuzken, diyet tedavisine uyumludur.

Objective: This descriptive study was conducted to investigate levels compliance to medication and diet therapy of patients_x000D_ with hypertension and individual factors that may affect compliance._x000D_ Methods: This study was conducted with the 250 patients who were volunteer and willing to participate in the study diagnosed with hypertension at least six months ago in a Hypertension Clinic of a University Hospital in Istanbul between the dates of November 1 December 31, 2011. Data were gathered by survey form, about Bliefs about Medication Compliance_x000D_ Scale (BMCS) and the Beliefs about Diet Compliance Scale (BDCS)._x000D_ Results: The mean age of the patients was 62.9±1.15.65.2% of the patients were female, 82% were married, 33.2% were primary school graduates, 67% had stress in their daily life, 44.4% had regular exercise and 55.2% had hypertension in their family._x000D_ The mean scores of the medication and diet benefit subscales of the patients who participated in our study(The benefit_x000D_ sub-dimension of the BMCS was 21.44±5.39, the benefit sub-dimension of the BDCS was 23.44±5.50)was found to be higher_x000D_ than the mean score of the sub-dimensions of the obstacle (The obstacle sub-dimension of the BMCS was 17.52±4.66, the_x000D_ obstacle sub-dimension of the BDCS was 12.9±3.59). Generally, the compliance of the patients who participated in our_x000D_ study to the medication treatment was found to be good and their adaptation to the dietary treatment was moderate. In_x000D_ the study, it was determined that patients who had hypertension in their families were compatible with medication and_x000D_ diet therapy, patients who exercised regular exercise were not compatible with medication, but were compatible with diet_x000D_ therapy and patients with stress in daily life were not compatible with medication and diet therapy (p<0.05)._x000D_ Conclusion: Patients who participated in the study had good levels of compliance with medication and diet therapy.Patients who have stress in their daily life decrease their level of compliance with medication and diet therapy.Patients with_x000D_ familial hypertension are more compatible with medication and diet therapy.Patients who are regularly exercising were not_x000D_ comply with medication therapy,but were compatible with diet therapy.
Levels Compliance to Medication and Diet Therapy of Patients with Hypertension